1995
DOI: 10.1056/nejm199512283332601
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Risk of Transmission of the Human Immunodeficiency Virus by Screened Blood in the United States

Abstract: The estimated risk of transmitting HIV by the transfusion of screened blood is very small and nearly half that estimated previously, primarily because the sensitivity of enzyme immunosorbent assays has been improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
146
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(158 citation statements)
references
References 22 publications
8
146
0
4
Order By: Relevance
“…Dixon B et al [3] reported chest tube output (CTO) as the strongest independent predictor of mortality [3]. Excessive hemorrhage results in the transfusion of allogenic blood products that expose the patient to multiple risks [4][5][6].…”
Section: Resultsmentioning
confidence: 99%
“…Dixon B et al [3] reported chest tube output (CTO) as the strongest independent predictor of mortality [3]. Excessive hemorrhage results in the transfusion of allogenic blood products that expose the patient to multiple risks [4][5][6].…”
Section: Resultsmentioning
confidence: 99%
“…Prior to 1995, one blood donation in every 210,000 to 1,140,000 in the United States was estimated to be from an HIV-infected individual during the window period, which is usually 22 to 25 days or longer (17). By implementing antigen screening of blood, an estimated four to six cases of transfusion-associated HIV infections may be prevented per year, lowering the estimated risk per unit transfused to a range of one in 562,000 to one in 825,000 (9,17). Therefore, it appears that antigen testing has utility for helping to protect the blood supply, though at a cost exceeding $60 million annually.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used methods rely on the detection of antibodies to HIV-1 in plasma or sera [2,[7][8][9]. Unfortunately, these techniques are of little value in the earliest stages of infection before the development of antibodies against HIV-1 (average infectious-window period of 25 days; 95% confidence interval: 9-41 days) [10][11][12][13][14] and also in neonates because maternal antibodies can persist in the newborn for up to 12 months or more [5,[15][16][17]. Detection of the major core protein of HIV-1 (p24 Gag) in serum or plasma by an ELISA is specific but does not offer the requisite sensitivity [5,6,[18][19][20][21].…”
mentioning
confidence: 99%